Frailty Phenotype and Healthcare Costs in Older Community-Dwelling Men: The MrOS study. (16th December 2020) - Ensrud, Kristine; Kats, Allyson; Langsetmo, Lisa Lisa; Vo, Tien; Schousboe, John
Abstract: To determine the association of the frailty phenotype with subsequent healthcare costs, we studied 1514 men (mean age 79.3 years) participating in the 2007-2009 exam linked with their Medicare claims data. The frailty phenotype (5 components) was categorized as robust, pre-frail or frail. Multimorbidity and a frailty indicator (approximating the deficit accumulation index) were derived from claims data. Functional limitations were assessed by asking about difficulty performing 5 IADL. Total direct healthcare costs were ascertained during 36 months following the exam. Mean annualized costs (2018 dollars) was 5707 among robust, 8964 among pre-frail and 20, 027 among frail men. Compared with robust, pre-frailty and frailty were each associated with higher costs after accounting for demographics, multimorbidity, functional limitations and the frailty indicator (cost ratio 1.18 [1.02-1.36] among pre-frail and 1.87 [1.47-2.39] among frail). Findings suggest that assessment of the phenotype may improve identification of individuals at increased risk of costly care.